2012
DOI: 10.5688/ajpe7610201
|View full text |Cite
|
Sign up to set email alerts
|

Redesign of a Required Undergraduate Pharmacy Management Course to Improve Student Engagement and Concept Retention

Abstract: Objective. To change the structure of a required pharmacy management course to make it more interactive and engaging for students. Design. The course is a required component of undergraduate curriculum and is completed over 2 semesters during the students' third year. Changes included requiring students to lead classroom discussions and complete a business plan in groups. Assessment. A questionnaire centering on methods of delivery, course content, and outcomes was distributed in 2 academic years, with 74.7% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 16 publications
4
26
0
1
Order By: Relevance
“…A similar approach was successfully adopted by Perepelkin to teach pharmacy students the importance of management within a community pharmacy context, with formation of a group-led business plan and presentation. 48 Faculty members involved with our project believed the hypothesis was correct : entrepreneurship and entrepreneurial skills were effectively promoted and enhanced through the workshop. The authors believed it was important to include all disciplines of pharmacy (community, hospital, and industry) in the workshop.…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach was successfully adopted by Perepelkin to teach pharmacy students the importance of management within a community pharmacy context, with formation of a group-led business plan and presentation. 48 Faculty members involved with our project believed the hypothesis was correct : entrepreneurship and entrepreneurial skills were effectively promoted and enhanced through the workshop. The authors believed it was important to include all disciplines of pharmacy (community, hospital, and industry) in the workshop.…”
Section: Discussionmentioning
confidence: 99%
“…Students in her class reported this to be an engaging and welcome change. Similarly, Perepelkin (2012) found that empowering pharmacy students through the use of self-directed learning increases student engagement. Studies such as these lead to the conclusion that when students are given the opportunity to decide for themselves what and how they will learn, they become more engaged in the learning process.…”
Section: Empowermentmentioning
confidence: 97%
“…The feedback sessions helped foster a collaborative community spirit during the exercise, giving students a feeling of belonging, which is known to stimulate attainment . Students also appreciated the task was something they would need to be able to do during professional practice and the undeniable relevance to their future careers created a very positive mindset ( anchored learning ) as seen in other studies .…”
Section: Discussionmentioning
confidence: 89%